Respuestas

2012-12-29T03:30:54+01:00

(x-2).(y+6)=360                                                                                                                        xy+6x-2=360                                                                                                                                                                                                                                                                          360+6x-2y-12=360                                                                                                                    6x-2y=12                                                                                                                                 3x-y=6                                                                                                                                     x=3x-6  y=3.(x-2)                                                                                                                      x.y=360                                                                                                                                   x.(3).(x-2)=360                                                                                                                         x.(x-2)=120                                                                                                                              x.(-2)=12.10                                                                                                                             x=12                          solucion: costo 12 soles.